Photoinduced diffraction grating in AgCl-Ag film on surface of silicone gel composition SYLGARD-184 - Ageev, L.A.; Galunov, N.Z.; Rieznikova, V.M.; Makovetsky, E.D.; Karavaeva, N.L.; Krech, A.V. (Functional Materials, 2016)
To extract and record scintillations, application of thin silver diffraction grating (DG) on fiber surface has been proposed, the fiber being based on gel composition SYLGARD-184. Such a grating has been formed in photosensitive composite AgCl-Ag film which was thermally deposited on the fiber surface in vacuum. This method has been shown to be suitable for making a film with required waveguide properties and photosensitivity. After irradiation with linearly polarized laser beam and after fixing removal of AgCl, a DG of Ag nanoparticles was obtained. Using diffraction from the DG, refractive index of the optical fiber has been measured. It has been shown that high dose of radiation exposure does not result in changes of properties of the sample obtained.